Pengaruh Upah Minimum Kabupaten/Kota (UMK) dan Pembangunan Manusia Berbasis Maqashid Syariah terhadap Jumlah Kemiskinan di Kabupaten Grobogan Jawa Tengah - Safitri, Ria; Baihaqi, Jadzil; Supriyadi, S. (Fakultas Ekonomi, UIN Maliki Malang, 2020)
This study aims to determine the effect of City Minimum Wage and human development based on maqashid shari'a on the amount of poverty in Grobogan, Central Java. This study uses a quantitative approach with secondary data types obtained from the Central Statistics Agency (BPS) and the Office of the Ministry of Religion Grobogan Regency. This research method uses multiple regression analysis techniques with time-series data from 2011 to 2017. Data analysis in this study uses Eviews 7 software. The results showed that the city minimum wage had a negative effect on the amount of poverty in Grobogan Regency. Whereas human development based on maqashid shari'a has a negative and not significant effect on the amount of poverty in Grobogan Regency. Human development based on maqashid shari'a has a negative and insignificant effect due to poverty measurement used by the Central Statistics Agency (BPS) using the concept of ability to meet basic needs (basic need approach). With this approach, poverty is seen as an inability from the economic side to meet the basic needs of food and non-food which are measured in terms of expenditure and income, so that other components cannot be directly linked to poverty.